2017
DOI: 10.1590/01047760201723022266
|View full text |Cite
|
Sign up to set email alerts
|

Fatalities in Wildland Fires From 1945 to 2015 in Sardinia (Italy)

Abstract: ABSTRACT:The worst outcome of wildland fires is the loss of human lives, a recurrent phenomenon over the last few decades in Sardinia, Europe and worldwide. This work analyzes all recorded fatalities in wildland fires in Sardinia from 1945 to 2015 and trends in terms of annual number of fatalities. This time period was split due to legal and socioeconomic changes periods (1945-1975; 1976-2000; 2001-2015). We classified accident types during wildland fires to study the most frequent causes of fatalities and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…These catastrophic events are mostly caused by humans, often ignite nearby urban areas or roads, spread for long distances, expose a large number of structures, and affect valued natural resources (Ager, Preisler, Arca, Spano, & Salis, 2014; Sergi Costafreda‐Aumedes, Comas, & Vega‐Garcia, 2017; Ricotta, Bajocco, Guglietta, & Conedera, 2018; Salis, Ager, Finney, Arca, & Spano, 2013). Indeed, the last 15 years have witnessed some of the most damaging wildfires ever experienced in southern EU countries, which have caused numerous causalties and substantial economic losses despite increasing investments in fire suppression (Cardil, Delogu, & Molina‐Terran, 2017; Moritz et al., 2014). While it has been suggested that improvements in prevention, detection, and suppression have largely contributed to the observed decreasing trends in the number of fires and area burned, large‐fire occurrence trends remain uncertain, depending on period of observation, study area and large‐fire definition threshold values (Jiménez‐Ruano, Rodrigues Mimbrero, & de la Riva Fernández, 2017; Raftoyannis et al., 2014; San‐Miguel‐Ayanz, Moreno, & Camia, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These catastrophic events are mostly caused by humans, often ignite nearby urban areas or roads, spread for long distances, expose a large number of structures, and affect valued natural resources (Ager, Preisler, Arca, Spano, & Salis, 2014; Sergi Costafreda‐Aumedes, Comas, & Vega‐Garcia, 2017; Ricotta, Bajocco, Guglietta, & Conedera, 2018; Salis, Ager, Finney, Arca, & Spano, 2013). Indeed, the last 15 years have witnessed some of the most damaging wildfires ever experienced in southern EU countries, which have caused numerous causalties and substantial economic losses despite increasing investments in fire suppression (Cardil, Delogu, & Molina‐Terran, 2017; Moritz et al., 2014). While it has been suggested that improvements in prevention, detection, and suppression have largely contributed to the observed decreasing trends in the number of fires and area burned, large‐fire occurrence trends remain uncertain, depending on period of observation, study area and large‐fire definition threshold values (Jiménez‐Ruano, Rodrigues Mimbrero, & de la Riva Fernández, 2017; Raftoyannis et al., 2014; San‐Miguel‐Ayanz, Moreno, & Camia, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the above, uncertainty still exists for some information because of the non-scientific nature of some data sources. Newspaper and periodical libraries have been used before as data sources in the study of natural hazards (Llasat et al 2009;Diakakis et al 2012;Cardil et al 2017), but they potentially add subjective information. To deal with this, the circumstances under which each incident occurred were described through a set of selected variables (shown in Table 2 and Fig.…”
Section: Data Quality and Uncertaintiesmentioning
confidence: 99%
“…Many catastrophic cases were recorded in recent years in Southern Europe (Viegas et al 2006;, some of them very lately (Diakakis et al 2016;Cardil et al 2017). As a reference, some of these remarkable forest fire events are:…”
mentioning
confidence: 99%
“…Table S2; [195][196][197] Firefighting personnel fatalities 4.86 The higher the number the higher the weight…”
Section: Broad Incident Categoriesmentioning
confidence: 99%